Sensors Fusion based Online Mapping and Features Extraction of Mobile Robot in the Road Following and Roundabout - Ali, Mohammed A. H.; Musa, Mailah; Wan Azhar, Wan Yusoff; Zamzuri, Hamedon; Zulkifli, Md. Yusof; Anwar, P. P. Abdul Majeed (IOP Publishing, 2016)
A road feature extraction based mapping system using a sensor fusion technique for mobile robot navigation in road environments is presented in this paper. The online mapping of mobile robot is performed continuously in the road environments to find the road properties that enable the robot to move from a certain start position to pre-determined goal while discovering and detecting the roundabout. The sensors fusion involving laser range finder, camera and odometry which are installed in a new platform, are used to find the path of the robot and localize it within its environments. The local maps are developed using camera and laser range finder to recognize the roads borders parameters such as road width, curbs and roundabout. Results show the capability of the robot with the proposed algorithms to effectively identify the road environments and build a local mapping for road following and roundabout.